2018
DOI: 10.1177/1049909118776985
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review for the Quality of End-of-Life Care for Patients With Dementia in the Hospital Setting

Abstract: Although patients with dementia appear to receive less aggressive treatment at the end of life, the provision of palliative care and symptom management may be inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
(171 reference statements)
2
16
0
Order By: Relevance
“…The uniqueness of this study is in its description of the clinical basis of palliative and EOL care for patients in the advanced stage of dementia ( Mitchell et al, 2009 ). Most of the studies conducted in the context of EOL care for patients with dementia in acute settings, as summarized in the review by Moon et al, (2018) refer to only one of the parameters that we examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniqueness of this study is in its description of the clinical basis of palliative and EOL care for patients in the advanced stage of dementia ( Mitchell et al, 2009 ). Most of the studies conducted in the context of EOL care for patients with dementia in acute settings, as summarized in the review by Moon et al, (2018) refer to only one of the parameters that we examined.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that up to 50% of healthcare providers in nursing homes fail to recognize dementia as a terminal illness ( Robinson et al, 2014 ), especially at its end stage ( Mitchell et al, 2009 ). In a systematic review, Moon et al (2018) found that those providing acute care to patients with dementia are increasingly aware of the terminal nature of end stage dementia; however, provision of EOL care was inconsistent. Healthcare professionals on acute hospital wards are usually trained to provide a quick diagnosis, cure disease, and save lives at any cost ( Dewing & Dijk, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the number of people dying with or from dementia continues to increase, the need for high quality, person-centred end-of-life care is a recognised priority [11]. However, guidelines for care and treatment are still primarily consensus-based, and suboptimal care continues to be reported across a range of end-of-life areas [12][13][14][15][16][17]. While people with dementia may be less likely to receive aggressive care at the end of life, provision of palliative care interventions and symptom management remains inconsistent [13].…”
Section: Introductionmentioning
confidence: 99%
“…1 Whilst family members may understand a dying person’s prognosis, 2 family members are often not prepared for death, 2,3 with inadequate information, emotional and bereavement support impacting family preparedness. 4 Family members of dying patients want expert, respectful and compassionate care, 5 anticipatory guidance 6 and to be supported in their distress. 7 When death is imminent, family members prefer to stay close to the dying person, 8 say goodbyes, 9 and to be supported in following their cultural rites and family traditions.…”
Section: Introductionmentioning
confidence: 99%